the cloud castle - Stilton, Thea; Thea Stilton
The Thea Sisters have received an urgent message from their friend Will Mystery. The magical Land of Clouds is in danger. The mouselets must find out why the clouds are disappearing! Once they enter the kingdom through Mount Everest, the mice meet fairies, elves, and unicorns on their way to the majestic Cloud Castle.
English